1976
DOI: 10.1063/1.322473
|View full text |Cite
|
Sign up to set email alerts
|

Near-uv photon efficiency in a TiO2 electrode: Application to hydrogen production from solar energy

Abstract: An n-type (001) TiO2 electrode irradiated at 365 nm was tested under anodic polarization: a saturation current independent of pH and proportional to light intensity has been observed. Accurate measurements of the incident power lead to a 60% photon efficiency. A photoelectrochemical cell built with such an electrode, operated under solar irradiation without concentration, produced an electrolysis current of 0.7 mA cm−2 without applied voltage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…The threshold of absorption for oven-made-n-WO 3 is at 475 nm (2.6 eV) which is in agreement with a bandgap value of 2.6 eV for n-WO 3 [74,75]. The low bandgap energy value of 2.42 eV for CM-p-WO 3 films can be attributed to the carbon incorporation during the flame oxidation process of tungsten metal sheet.…”
Section: Uv-vis Spectra On Cm-p-wosupporting
confidence: 77%
See 1 more Smart Citation
“…The threshold of absorption for oven-made-n-WO 3 is at 475 nm (2.6 eV) which is in agreement with a bandgap value of 2.6 eV for n-WO 3 [74,75]. The low bandgap energy value of 2.42 eV for CM-p-WO 3 films can be attributed to the carbon incorporation during the flame oxidation process of tungsten metal sheet.…”
Section: Uv-vis Spectra On Cm-p-wosupporting
confidence: 77%
“…Tungsten trioxide (WO 3 ) is also of great interest and has been investigated extensively due to its promising physical and chemical properties [70][71][72][73] The WO 3 films are nontoxic and have relatively low price. Semiconducting tungsten oxide (WO 3 ) is an interesting candidate for photocataylsis because of its relatively low bandgap energy (E g = 2.6 eV), [74][75][76] resulting in possible utilization of 12% of the solar spectrum [77]. Spectral response studies were carried out for n-type WO 3 by different workers [78,79].…”
Section: Development Of Photoelectrodes For Water Splittingmentioning
confidence: 99%
“…1) would not be expected, if hole transfer processes (in case of low surface state density) or recombination (involving dense surface states) played a significant role considering either the kinetics or the quantitative contribution to the gross photoeffect. This conclusion can also been drawn by means of steady state measurements of luxampere dependence at low and moderate intensities [33]. f) Finally, it can be suggested that the process of separation and transit of photogenerated carriers through the depletion layer rules the kinetics of the photoresponse, if no additional RC-shaping occurs.…”
Section: Discussionmentioning
confidence: 80%
“…In sunlight with a measured intensity of 105 mW/cm2, the conversion efficiency (defined as the ratio of the energy stored in the hydrogen produced to the energy of the incident sunlight) was found to be as high as 1.3% for AE-doped Ti02 cells. A sunlight conversion efficiency of 0.4% had been reported earlier for undoped Ti02' and a value of 0.6% (54) was published more recently (55). Another report (56) has been shown to be constant…”
Section: -3 From a Carrier Concentration Of 10mentioning
confidence: 71%